Recent climate-induced shape changes of the ice summit of Kebnekaise, Northern Sweden. Issue 1 (2nd January 2019) - Holmlund, Per; Holmlund, Erik S.
ABSTRACT: The ice summit of Kebnekaise is slowly melting down as a consequence of climate change. In August 2018 this peak, which for a long time has been the highest in Sweden, reached an elevation a few decimetres lower than the nearby situated northern summit in solid rock. It has become a symbol of the fragility of nature. Its areal extent and shape have varied over time and its height has ranged within approximately 15 m during the twentieth century. Since the turn of the century, the ice summit has decreased to a new lower and smaller level but the changes are not uniform, and they show a complex relation between weather parameters and the shape and size of the summit. Layers in the ice include climate information of past changes. But what changes are we able to determine by examining gradually exposed dust layers, or by coring the summit. In this paper, we are analysing the late changes in shape and volume of the ice summit and we place the results into a paleo climate discussion. We have used photogrammetric methods to map the geometry of the summit at different dates when data has been available. We have also done a multiple regression to analyse the relation between the summit elevation and the net mass balance of the nearby located Storglaciären. The correlation is good from mid 1970s until now but weak prior to that. It is herein explained by former uncertainties of the geographic position of the summit.